Answer:
The answer would have to be B
To solve for f, you need to isolate/get the variable by itself in the equation:
4(0.5f - 0.25) = 6 + f Distribute 4 into (0.5f - 0.25)
(4)0.5f + (4)(-0.25) = 6 + f
2f - 1 = 6 + f Subtract f on both sides to get "f" on one side of the equation
2f - f - 1 = 6 + f - f
f - 1 = 6 Add 1 on both sides to get "f" by itself
f - 1 + 1 = 6 + 1
f = 7
PROOF
4(0.5f - 0.25) = 6 + f Substitute/plug in 7 into "f" since f = 7
4(0.5(7) - 0.25) = 6 + 7
4(3.5 - 0.25) = 13
4(3.25) = 13
13 = 13
No. x cannot equal 2 and 7
Answer:
x + y = 5
<u>3x - 4y = 8</u><u> </u><u> </u><u> </u>
3x + 3y = 15
<u>3x - 4y = 8 </u>-
7y = 7
y = 1
x + y = 5
x + 1 = 5
x = 4
x = 4
y = 1
Hope it helps!